Docosahexaenoyl ethanolamide improves glucose uptake and alters endocannabinoid system gene expression in proliferating and differentiating C2C12 myoblasts - Kim, Jeffrey; Carslon, Morgan; Watkins, Bruce A. (Frontiers in Physiology, 2014)
Skeletal muscle is a major storage site for glycogen and a focus for understanding insulin resistance and type-2-diabetes. New evidence indicates that overactivation of the peripheral endocannabinoid system (ECS) in skeletal muscle diminishes insulin sensitivity. Specific n-6 and n-3 polyunsaturated fatty acids (PUFA) are precursors for the biosynthesis of ligands that bind to and activate the cannabinoid receptors. The function of the ECS and action of PUFA in skeletal muscle glucose uptake was investigated in proliferating and differentiated C2C12 myoblasts treated with either 25µM of arachidonate (AA) or docosahexaenoate (DHA), 25µM of EC [anandamide (AEA), 2-arachidonoylglycerol (2-AG), docosahexaenoylethanolamide (DHEA)], 1µM of CB1 antagonist NESS0327, and CB2 antagonist AM630. Compared to the BSA vehicle control cell cultures in both proliferating and differentiated myoblasts those treated with DHEA, the EC derived from the n-3 PUFA DHA, had higher 24 h glucose uptake, while AEA and 2-AG, the EC derived from the n-6 PUFA AA, had lower basal glucose uptake. Adenylyl cyclase mRNA was higher in myoblasts treated with DHA in both proliferating and differentiated states while those treated with AEA or 2-AG were lower compared to the control cell cultures. Western blot and qPCR analysis showed higher expression of the cannabinoid receptors in differentiated myoblasts treated with DHA while the opposite was observed with AA. These findings indicate a compensatory effect of DHA and DHEA compared to AA-derived ligands on the ECS and associated ECS gene expression and higher glucose uptake in myoblasts. Key Words: endocannabinoid system •C2C12 myoblasts cannabinoid receptors glucose uptake gene expression DHEA • polyunsaturated fatty acids